Impact of the Multiple Sclerosis-Associated Genetic Variant CD226 Gly307Ser on Human CD8 T-Cell Functions - Morandi, Elena (2024)
The rs763361 nonsynonymous variant in the CD226 gene, which results in a glycine-to-serine substitution at position 307 of the CD226 protein, has been implicated as a risk factor of various immune-mediated diseases, including multiple sclerosis (MS). Compelling evidence suggests that this allele may play a significant role in predisposing individuals to MS by decreasing the immune-regulatory capacity of Treg cells and increasing the proinflammatory potential of effector CD4 T cells. However, the impact of this CD226 gene variant on CD8 T-cell functions, a population that also plays a key role in MS, remains to be determined.